Women's Travel Writing of the 1920s and 1930s - Hoag, Ann (Trinity College Dublin, 2007)
The decades following World War One saw an explosion of international movement including the migration of colonized subjects towards imperial capitals and artistic expatriates attracted to distant communities. The advent of travel technologies minimized geographical distances and made travel accessible to a wider population. Perhaps as a reaction to the extensive confinement and restriction on movement during the war, the 1920s and 1930s arguably marked the golden age of travel. Women of this period were allowed relative freedom to voyage and explore in contrast to their nineteenth century counterparts, yet the residual association between women and domesticity impacted women's experiences in distant locations. The focus of my research is on European women's travel writing that emerged during these years. I am interested in how these authors explored a territory 'elsewhere' beyond the limitations of home, and how their negotiations of traditional male travel narratives resulted in a remapping of literary space. I hope to scrutinize how these women's movements across national borders translated into a challenge of gender boundaries, and the implications of their writing on perceptions of history and imperialism.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Women's travel writing; Twentieth-century literature